Uncommon sense the strangest ideas from the smartest philosophers - Pessin, Andrew 1962- (Rowman & Littlefield Publishers, Inc., 2012)
"In Uncommon Sense, Andrew Pessin leads us on an entertaining tour of philosophy, explaining the pivotal moments when the greatest minds solved some of the knottiest conundrums--by asserting some very strange things. But the great philosophers don't merely make unusual claims, they offer powerful arguments for those claims that you can't easily dismiss. And these arguments suggest that the world is much stranger than you could have imagined: You neither will, nor won't, do certain things in the future, like wear your blue shirt tomorrow ; But your blue shirt isn't really blue, because colors don't exist in physical objects; they're only in your mind ; Time is an illusion ; Your thoughts are not inside your head ; Everything you believe about morality is false ; Animals don't have minds ; There is no physical world at all. In eighteen lively, intelligent chapters, spanning the ancient Greeks and contemporary thinkers, Pessin examines the most unusual ideas, how they have influenced the course of Western thought, and why, despite being so odd, they just might be correct. Here is popular philosophy at its finest, sure to entertain as it enlightens."--Publisher's website